46‐2: Distinguished Paper: Dynamic Real World Objects in Augmented and Virtual Reality Applications. Issue 1 (May 2017) - Ebner, Thomas; Feldmann, Ingo; Renault, Sylvain; Schreer, Oliver
Abstract : We present a flexible algorithmic pipeline for high‐quality three‐dimensional acquisition of dynamic real world objects. In this context we discuss the reduction of mesh complexity as one of the key challenges for visualizing reconstructed three‐dimensional content in augmented and virtual reality applications.